Physical Acoustics in the Solid State - Lüthi, Bruno. (Springer Series in Solid-State Sciences,, 2005)
Suitable for researchers and graduate students in physics and material science, "Physical Acoustics in the Solid State" reviews the modern aspects in the field, including many experimental results, especially those involving ultrasonics. Practically all fields of solid-state physics are covered: metals, semiconductors, magnetism, superconductivity, different kinds of phase transitions, low-dimensional systems, and the quantum Hall effect. After a review of the relevant experimental techniques and an introduction to the theory of elasticity, emphasizing the symmetry aspects, applications in the various fields of condensed matter physics are presented. Also treated are Brillouin-scattering results and results from thermodynamic investigations, such as thermal expansion and specific heat.